Disney Dumbo - Autumn; Publishing ([Northamptonshire Autumn Publishing, 2019)
Dumbo is a young elephant with huge ears, who lives in a circus. Teased for his ears, he is lonely, but makes a few friends such as Timothy the mouse. One night, during a performance, he discovers that he can fly by flapping his ears, and becomes a hero